Vowel harmony in Shigatse Tibetan - Haller, Felix (2024)
Vowel harmony is a phenomenon in which potentially all vowels in adjacent moras or syllables within a domain, such as a phonological or morphological word, systematically agree with each other with regard to one or more articulatory features. Common features include [±high/ ±low], [±back], [±ATR] (Advanced Tongue Root) and [±round]. The present paper provides new insights into the system of vowel harmony of the western Central Tibetan dialect of Shigatse, which is dependent on the tonal system because of its relation to whether a syllable carries a tone or not. The findings presented in this article corroborate the accounts of other Tibetan dialects which are also reported to possess height harmonies. A special position in the system is occupied by the neutral diphthong ie because it causes raising under certain conditions but is not itself affected by vowel harmony.